PENGARUH MANAJEMEN WAKTU BELAJAR PESERTA DIDIK KELAS 5 SDN SALATIGA 05 TERHADAP NILAI RAPORT - Indra Kartika Sari (Universitas Pakuan, 2019)
THE EFFECT OF LEARNING TIME MANAGEMENT AGAINST RAPORT VALUE STUDENTS OF CLASS 5 SDN SALATIGA 05This research intended to determine the effect of learning time management towards first semester score report on the fifth grade students at SDN 05, Salatiga, Central Java. The method of the study is the quantitative descriptive method. The technique of collecting the data is by sharing questionare and documentation therefor data analysis method is using the simple percentage. The data source taken from the fifth grade students input and their first semester report document at SDN 05, Salatiga. The result of the study show that the fifth grade students at SDN think that learning is an activity that must be done 100%, that means all students are aware that learning is a thing must be done. 72% of the students manage their study time at home. 80% of the top 10 rank students manage their time to study at home, this percentage is higher than the percentage of those who are not in the top 10 rank and the number is only 68% of 19 students. Learning time management affects the result of the score report because 80% of the top 10 manage their learning time and all of them pass the passing grade. This percentage of the students who manage their study time is higher than those who are below the top 10 rank which is only 68% of 19 students and there are some students in the top 10 still don’t pass the passing grade.